Centralization of Services for Children Born with Orofacial Clefts in the United Kingdom: A Cross-Sectional Survey. (September 2014) - Scott, Julia K.; Leary, Sam D.; Ness, Andy R.; Sandy, Jonathan R.; Persson, Martin; Kilpatrick, Nicky; Waylen, Andrea E.
Objective: To examine current provision of cleft lip and/or palate services in the U.K. and compliance with recommendations made by the Clinical Standards Advisory Group (CSAG) in 1998. Design: Cross-sectional questionnaire survey. Setting: All 11 services within the U.K. providing care for children born with a cleft lip and palate. Participants: Members from each healthcare specialty in each U.K. cleft team. Interventions: Self-administered postal questionnaires enquired about the provision of cleft services. Data were collected about the overall cleft service, team coordination, hearing, orthodontics, pediatric dentistry, primary cleft surgery, psychology, restorative dentistry, secondary surgery, specialist cleft nursing, and speech and language therapy. Results: Questionnaires were returned from members of 130/150 cleft teams (87%) and these showed that U.K. cleft services have been restructured to 11 centralized services with 17 primary operative sites and 61 peripheral sites. All services provide care through a multidisciplinary (MDT) model, but the composition of each team varies. Primary cleft surgery and orthodontics were the only specialties that were represented in all cleft teams. Specialties may be represented in a team but their attendance at MDT clinics is variable. Only one team met all of the CSAG recommendations. Conclusions: Our survey shows that cleft services have centralized over the last 10 years, and an MDT model of care has been adopted. Further research is needed to show how this has influenced outcomes and to see whether some models of centralized care are associated with better outcomes.